Antibodies Are Required for Complete Vaccine-Induced Protection against Herpes Simplex Virus 2. - William P Halford; Joshua Geltz; Ronald J Messer; Kim J Hasenkrug (PLoS ONE, 2015)
Herpes simplex virus 2 (HSV-2) 0ΔNLS is a live HSV-2 ICP0- mutant vaccine strain that is profoundly attenuated in vivo due to its interferon-hypersensitivity. Recipients of the HSV-2 0ΔNLS vaccine are resistant to high-dose HSV-2 challenge as evidenced by profound reductions in challenge virus spread, shedding, disease and mortality. In the current study, we investigated the requirements for HSV-2 0ΔNLS vaccine-induced protection. Studies using (UV)-inactivated HSV-2 0ΔNLS revealed that self-limited replication of the attenuated virus was required for effective protection from vaginal or ocular HSV-2 challenge. Diminished antibody responses in recipients of the UV-killed HSV-2 vaccine suggested that antibodies might be playing a critical role in early protection. This hypothesis was investigated in B-cell-deficient μMT mice. Vaccination with live HSV-2 0ΔNLS induced equivalent CD8+ T cell responses in wild-type and μMT mice. Vaccinated μMT mice shed ~40-fold more infectious HSV-2 at 24 hours post-challenge relative to vaccinated wild-type (B-cell+) mice, and most vaccinated μMT mice eventually succumbed to a slowly progressing HSV-2 challenge. Importantly, passive transfer of HSV-2 antiserum restored full protection to HSV-2 0ΔNLS-vaccinated μMT mice. The results demonstrate that B cells are required for complete vaccine-induced protection against HSV-2, and indicate that virus-specific antibodies are the dominant mediators of early vaccine-induced protection against HSV-2.